Symbolic Construction of Homeland in Zoulfa Katouh’s As Long As The Lemon Trees Grow - Shabrina Fauziyyah; Lili Awaludin; Dian Nurrachman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Syrian diaspora literature often engages with the experience of displacement by keeping the homeland alive through imagination. This study examines how Zoulfa Katouh's debut novel, As Long as the Lemon Trees Grow (2022), uses plant and environmental imagery to symbolically construct the meaning of homeland within a Syrian diaspora context. Previous studies have addressed trauma, ecology, and romantic narrative, but none has closely examined how the novel’s recurring natural imagery functions as a structured symbolic strategy. This study fills that gap by analyzing selected textual passages containing recurring natural imagery to show how these images accumulate meaning and construct a sense of belonging throughout the narrative. The analysis draws on Stuart Hall's (1997) theory of representation, Northrop Frye's (1957) theory of literary symbolism and diaspora scholarship by Rushdie (1991), Safran (1991), and Brah (1996), applying textual analysis and close reading as its method. The findings reveal two interconnected symbolic patterns. First, plant imagery, including the daisy, jasmine, and the lemon tree, follows a symbolic trajectory from personal memory and emotional comfort toward collective endurance and imagined homeland. Second, environmental imagery, including trapped moonlight, rain, sunset, and the Mediterranean Sea, reflects the emotional conditions of siege, loss, and departure. Together, these patterns suggest that homeland in the novel is not a fixed territory but as an ongoing symbolic construction sustained through memory, sensory experience, and emotional attachment. Through an integrated application of Hall and Frye, this study demonstrates that natural imagery can serve as a primary medium for representing displacement and belonging in contemporary Syrian diaspora fiction.